Promising tubers for industrial revolution - Jyothi, A. N.; Sajeev, M. S.; Padmaja, G. (Indian Horticulture, 2019)
There is immense scope for cassava for valueaddition and product diversification to properly exploit the developmental elasticity of cassava. Creating awareness about immense scope of cassava for valueaddition and product diversification is absolutely essential to properly exploit cassava. A shift from rural markets to semi-urban and urban markets is also visualized globally, which also can enhance the market demand for value-added, ready-to-eat food products. Transition from subsistence agriculture to marketoriented agriculture has its base in agri-business units set up in rural and producing areas. The scope for biotechnological intervention in tuber crops is enormous as it can lead to the production of a whole range of products that can find use in the food, textile, pharmaceutical, beverage and confectionery industries. Nevertheless, tapping the potential by identifying the most appropriate microbial strains, standardizing and optimizing the culture conditions, economizing the production etc. are vital for maximizing their use in the years to come.